Design and analysis of a two-degrees-of-freedom monolithic compliant piezoelectric microgripper. (October 2022) - Song, Shuaiguan; Yang, Yiling; Fu, Lei; Li, Guoping; Wei, Yanding
This paper presents the design, modeling, and testing of a compliant two-degrees-of-freedom microgripper using a single piezoelectric actuator. It can move along the x - and y -directions by combining double-leaf bridge and parallelogram mechanisms. An analytical model is established using the finite-element method. The displacement amplification ratio, natural frequency, and output coupling ratio are analyzed using ANSYS software. An experimental test system is built to verify the open-loop performances. Experimental results show that the displacement amplification ratios in the x - and y -directions are 30.8 and 8.6. The first resonant frequencies in the x - and y -directions are 123.3 and 546.9 Hz. If an input displacement of 10 μm is applied, the operating ranges in the x - and y -directions are 0–616.6 μm and 0–51.0 μm, and the gripping force range is 0–25.8 mN. Experimental results validate the feasibility of the theoretical model and simulation analysis. Also, closed-loop trajectory control is conducted to reduce the hysteresis nonlinearity and achieve a high control accuracy for the new microgripper.